ANALISIS PENDAPATAN DAN TENAGA KERJA PADA SEKTOR PERTANIAN TERHADAP PERTUMBUHAN EKONOMI DI SUMATERA BARAT - Masdawia, Masdawia; Nengsih, Novia (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This study aims to determine the influence of income and labor in the agricultural sector on economic growth in West Sumatra Province in 2008-2023. This research is a field research with a quantitative approach. This study uses secondary data on income and labor in the agricultural sector of West Sumatra from 2008-2023. Data collection techniques using documentation and Multiple Linear Regression Analysis techniques. The results of the study prove that income in the agricultural sector has a positive and significant effect on West Sumatra's economic growth in 2008 – 2023. Labor in the agricultural sector has a positive and significant effect on West Sumatra's economic growth in 2008-2023. Simultaneously, income and labor in the agricultural sector have a positive and significant effect on the economic growth of West Sumatra Province in 2008-2023. The R-Square value of 0.683 or 68.3 percent of the independent variables affected the dependent variables, while the rest were influenced by other variables that were not mentioned in this study.